Current Issues in Normative and Legal Regulation of Crime Prevention in Ukraine: Necessity for Improvement (Bulletin of Kharkiv National University of Internal Affairs, 2025)
The article reflects the actual state of legal regulation of activities aimed at preventing crimes and other offences in Ukraine. Undoubtedly, there are problematic aspects and a necessity for improvement.In particular, Ukraine currently lacks an adequate legislative framework for the prevention of offences that would correspond to the growing level of crime and threats to Ukraine's national security. In the absence of a special law, a significant part of the organisational issues of offence prevention is regulated by the statutes and, consequently, by departmental regulations.There are also problematic issues in law enforcement practices regarding crime prevention: such activities focus not on the causes and conditions of crime and its development, but on the end results of criminal activity, which are mainly addressed through repressive measures. The insufficient level of professional training of the staff involved affects the effectiveness of crime prevention.As a result, law enforcement agencies give priority to repressive measures and do not pay sufficient attention to the prevention of offences: it is often carried out in an unsystematic, situational manner and to the minimum extent necessary, and therefore remains insufficiently implemented in the practice of Ukrainian law enforcement agencies.Based on the results, measures to improve legislative regulation of prevention in Ukraine have been proposed. It is necessary to adopt the law ‘On the Fundamentals of Crime Prevention’ and to develop regulatory and legal acts at the state and departmental levels aimed at its implementation and to ensure their implementation. The process of training and educating law enforcement officers in legal awareness requires constant improvement.
Keywords: crimes; offences; prevention; regulatory and legal regulation; problems; improvement.